The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/foods11142150
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments and Applications of Nanosystems in the Preservation of Meat and Meat Products

Abstract: Due to their high water, lipid, and protein content, meat and meat products are highly perishable. The principal spoilage mechanisms involved are protein and lipid oxidation and deterioration caused by microbial growth. Therefore, efforts are ongoing to ensure food safety and increase shelf life. The development of low-cost, innovative, eco-friendly approaches, such as nanotechnology, using non-toxic, inexpensive, FDA-approved ingredients is reducing the incorporation of chemical additives while enhancing effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…Nano/microcapsules which function continuously during the processing, storage, and distribution of meat products have been discussed recently. 409 Abbaspourrad and coworkers 406 fabricated chondroitin sulfate (CHS)/chitosan (CS) microcapsules via layer-by-layer assembly (LbL) as carriers for co-pigmented ANs. Co-pigmentation with CHS of moderate concentration increased the encapsulation efficiency of anthocyanin, favored anthocyanin retention in the microcapsule and improved the prolonged release of anthocyanin in a simulated gastrointestinal environment.…”
Section: Food and Packagingmentioning
confidence: 99%
“…Nano/microcapsules which function continuously during the processing, storage, and distribution of meat products have been discussed recently. 409 Abbaspourrad and coworkers 406 fabricated chondroitin sulfate (CHS)/chitosan (CS) microcapsules via layer-by-layer assembly (LbL) as carriers for co-pigmented ANs. Co-pigmentation with CHS of moderate concentration increased the encapsulation efficiency of anthocyanin, favored anthocyanin retention in the microcapsule and improved the prolonged release of anthocyanin in a simulated gastrointestinal environment.…”
Section: Food and Packagingmentioning
confidence: 99%
“…During the pandemic, food waste caused by excessive food hoarding has accounted for the vast majority of total food waste in urban households. To reduce food waste, in addition to developing low-cost, innovative, eco-friendly approaches such as nanotechnology, using non-toxic, inexpensive, FDA-approved ingredients to guarantee the extension of food shelf-life while minimally affecting its organoleptic, nutritional, and sensory properties [ 60 , 61 ] becomes a necessary coping strategy to be used in conjunction with efforts to guide residents away from irrational hoarding behavior. Considering that previous studies have not revealed enough about the behavioral mechanism of citizens’ irrational food hoarding, it is necessary to carry out prospective exploration of this topic, and the relevant results will be of great value to the public policy design of food waste management.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic preservatives such as butyrate hydroxyanisole (BHA), butyrate hydroxytoluene (BHT), and tertiary butyl hydroquinone (TBHQ), when consumed in excess amounts, can cause gene mutations and carcinogenic effects [12]. In addition, the FDA recommends using environmentally friendly ingredients and reducing chemicals in food products [81]. Natural ingredients were chosen as an alternative to synthetic preservatives and to ease concerns about resistance to microbial pathogens [82].…”
Section: Functionality Improvement Of Meat Productmentioning
confidence: 99%
“…Steps that can be taken to reduce and stop this toxicity include dosage restrictions, specialized nanoemulsion applications, the ideal nano-size design that does not promote material infiltration into cell organelles [96], and the use of health-safe stabilizers and bioactive substances [81]. Production of nanoemulsions utilizing high-energy technologies on a laboratory scale is not cost-effective for industrial use [19].…”
Section: E T E Dmentioning
confidence: 99%